YlxM Is a Newly Identified Accessory Protein That Influences the Function of Signal Recognition Particle Pathway Components in Streptococcus mutans - Williams, Matthew L. (American Society for Microbiology, 2014)
Streptococcus mutans is a cariogenic oral pathogen whose virulence is determined largely by its membrane composition. The signal recognition particle (SRP) protein-targeting pathway plays a pivotal role in membrane biogenesis. S. mutans SRP pathway mutants demonstrate growth defects, cannot contend with environmental stress, and exhibit multiple changes in membrane composition. This study sought to define a role for ylxM, which in S. mutans and numerous other bacteria resides directly upstream of the ffh gene, encoding a major functional element of the bacterial SRP. YlxM was observed as a produced protein in S. mutans. Its predicted helix-turn-helix motif suggested that it has a role as a transcriptional regulator of components within the SRP pathway; however, no evidence of transcriptional regulation was found. Instead, capture enzyme-linked immunosorbent assay (ELISA), affinity chromatography, and bio-layer interferometry (BLI) demonstrated that S. mutans YlxM interacts with the SRP components Ffh and small cytoplasmic RNA (scRNA) but not with the SRP receptor FtsY. In the absence of FtsY, YlxM increased the GTP hydrolysis activity of Ffh alone and in complex with scRNA. However, in the presence of FtsY, YlxM caused an overall diminution of net GTPase activity. Thus, YlxM appears to modulate GTP hydrolysis, a process necessary for proper recycling of SRP pathway components. The presence of YlxM conferred a significant competitive growth advantage under nonstress and acid stress conditions when wild-type and ylxM mutant strains were cultured together. Our results identify YlxM as a component of the S. mutans SRP and suggest a regulatory function affecting GTPase activity.